Combination Effect of Methanol Extract of Hibiscus rosasinensis L. Leaf and Ciprofloxacin against Shigella dysentriae In Vitro - Billy Jusup Kurniawan; Muhammad Ali Shodikin; Bagus Hermansyah (Journal of Agromedicine and Medical Sciences, 2018)
One of way to preventing bacterial resistance is a combination of natural plant products with antibiotics. Hibiscus rosasinensis leaf proved to have antibacterial activity against Shigella dysentriae. Ciprofloxacin is the first-choice antibiotic to treat Shigella dysentriae infection. The purpose of this study was to determine the effect of methanol extract of Hibiscus rosasinensis leaves and ciprofloxacin against S. dysentriae bacteria in vitro. The type of this study was quasi experimental design with posttest only control group design using nine treatment groups (with concentration variation of 0.5 μg / mL, 1 μg / mL, 2 μg / mL, 4 μg / mL, 8 μg / mL, 16 μg / mL, 32 μg / mL, 64 μg / mL, and 128 μg / mL with 5 μg / 5 μL ciprofloxacin) and one control group (only 5 μg / 5 μL ciprofloxacin). The method used was agar well diffusion. The data was the diameter of inhibition zone around the well. The results showed that the variant of hibiscus leaf concentration could inhibit the growth of Shigella dysentriae but formed smaller inhibition zone diameter than ciprofloxacin alone. Keywords: combination, hibiscus rosasinensis leaf, ciprofloxacin, Shigella dysentriae